Different human papillomavirus types share early natural history transitions in immunocompetent women. Issue 6 (17th June 2022) - Adebamowo, Sally N.; Befano, Brian; Cheung, Li C.; Rodriguez, Ana Cecilia; Demarco, Maria; Rydzak, Greg; Chen, Xiaojian; Porras, Carolina; Herrero, Rolando; Kim, Jane J.; Castle, Philip E.; Wentzensen, Nicolas; et al.
Abstract: Necessary stages of cervical carcinogenesis include acquisition of a carcinogenic human papillomavirus (HPV) type, persistence associated with the development of precancerous lesions, and invasion. Using prospective data from immunocompetent women in the Guanacaste HPV Natural History Study (NHS), the ASCUS‐LSIL Triage Study (ALTS) and the Costa Rica HPV Vaccine Trial (CVT), we compared the early natural history of HPV types to inform transition probabilities for health decision models. We excluded women with evidence of high‐grade cervical abnormalities at any point during follow‐up and restricted the analysis to incident infections in all women and prevalent infections in young women (aged <30 years). We used survival approaches accounting for interval‐censoring to estimate the time to clearance distribution for 20 529 HPV infections (64% were incident and 51% were carcinogenic). Time to clearance was similar across HPV types and risk classes (HPV16, HPV18/45, HPV31/33/35/52/58, HPV 39/51/56/59 and noncarcinogenic HPV types); and by age group (18‐29, 30‐44 and 45‐54 years), among carcinogenic and noncarcinogenic infections. Similar time to clearance across HPV types suggests that relative prevalence can predict relative incidence. We confirmed that there was a uniform linear association between incident and prevalent infections for all HPV types within each study cohort. In the absence of progression to precancer, we observed similar time to clearance for incident infections across HPV types and risk classes. A singular clearance function for incident HPV infections has important implications for the refinement of microsimulation models used to evaluate the cost‐effectiveness of novel prevention technologies. Abstract :